(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Work- life balance is the matter of concern in 21st century. It is really tough to strike a balance between family and work in this competitive era. One has to understand that work life and personal life are the two sides of the same coin. It is very difficult for an individual to fulfill the demands of both professional as well as personal life. Now- a- days an individual may find himself working continuously from 7 a.m. to 11 p.m., even answering email and calls during mealtime. Work easily invades our personal lives because of the simple fact that money dominates the modern life. When there’s no balance in personal and professional life it leads to loss in productivity and too often it affects the individual’s health. This research paper is an attempt to study the work life balance issues with reference to nurses working in west Delhi area as well as the factors that determine work life balance.